Thrilled to have ‘bagged a bargain’ or ‘bitter’ and ‘very frustrating’?: exploring consumer attitudes to value and deals in the leisure travel market - McCabe, Scott; Branco Illodo, Ines (SAGE, 2018)
Similar to most global tourism markets, UK consumers adjusted their behavior during the global financial crisis, emphasizing value for money in travel choices. However, there is little evidence concerning consumers’ value-seeking behavior and especially how deals, discounts and other sales promotions influence tourist decision making. This project explores concepts of value consciousness and deal proneness to shed light on attitudes towards monetary value in travel purchases. Using focus groups, the study found that deals and discounts frequently underpin some tourist choices, but that value consciousness is related to deal proneness, and interactions between the two could result in negative, positive or mixed emotions. This relationship was captured through a dynamic categorization of tourists’ attitudes and behavior into four approaches to deals and value, namely deals 1) as a way of life, 2) as a bonus, 3) as a problem and 4) as toxic. The categories were dynamic in that individuals could move across them. The implications for tourism marketers are outlined.